"A ton of faith in science!" Nature and role of assumptions in, and ideas about, science and epistemology generated upon watching a sci‐fi film. Issue 8 (15th April 2016) - Myers, John Y.; Abd‐El‐Khalick, Fouad
Abstract: This study (i) explicates the sorts of ideas about science and the nature of knowing that were generated among participant graduate students who viewed the sci‐fi film, Contact, and (ii) examines the interactions between these ideas and ontic stances with which participants approached viewing the film. Eleven doctoral students of various disciplinary backgrounds viewed Contact, wrote a film review in response to a prompt, and were interviewed to clarify and further explore ideas mentioned in their review. Participants' most prevalent ideas generated upon viewing Contact were that scientific assumptions, and trust in scientific knowledge and authority, are "faith‐based"; theory‐choice in science can be faith‐based; science requires empirical evidence; and females in science are severely misrepresented. Further, more participants experienced such ideas as realistic rather than unrealistic representations of science, and some identified with particular scenes from the film. These results do not empirically support pedagogical techniques recommended by prior literature suggesting that science teachers who expose students to sci‐fi film in the classroom should focus specifically on what teachers deem scientifically inaccurate or misinformation. This approach is rather limited and fails to consider ideas generated by students upon viewing films, which teachers might not expect (e.g., relating science with faith). Rather, we recommend an open‐ended, reflective pedagogical approach to using sci‐fi film where teachers, first, openly engage students with writing about and discussing thoughts they generate upon watching a given film, and then move to address student ideas. Our findings also indicate a critical need to expand the current consensus model for NOS in K‐12 science education—in particular, including and explicating the nature and role of assumptions in science as an additional core dimension of currently accepted NOS models. Toward this end, we delineate the nature and role of scientific assumptions by reference to the epistemological theory of coherentism. © 2016 Wiley Periodicals, Inc. J Res Sci Teach 53: 1143–1171, 2016